2022
DOI: 10.3389/fimmu.2022.991928
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 persistence and leukemogenesis: A game of hide-and-seek with the host immune system

Abstract: Human T-cell leukemia virus type 1 (HTLV-1), a retrovirus which mainly infects CD4+ T cells and causes adult T-cell leukemia/lymphoma (ATL), is primarily transmitted via direct cell-to-cell transmission. This feature generates a wide variety of infected clones in hosts, which are maintained via clonal proliferation, resulting in the persistence and survival of the virus. The maintenance of the pool of infected cells is achieved by sculpting the immunophenotype of infected cells and modulating host immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 131 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Alterations in immune responses are associated with HTLV-1 infection and contribute to disease development [ 10 , 27 , 28 , 71 , 72 , 73 , 74 ]. While CD4 cells are the primary target of HTLV-1, the virus is also found in CD8, monocytes, macrophages, and dendritic cells from infected individuals [ 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in immune responses are associated with HTLV-1 infection and contribute to disease development [ 10 , 27 , 28 , 71 , 72 , 73 , 74 ]. While CD4 cells are the primary target of HTLV-1, the virus is also found in CD8, monocytes, macrophages, and dendritic cells from infected individuals [ 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune dysregulation is a common feature in HTLV-1 infection [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and although there is a strong innate and adaptive response to the virus, it results in a lifelong persistent infection of primarily T lymphocytes [ 21 , 22 , 23 , 24 , 25 , 26 ]. This is likely linked to the ability of the virus to counteract host responses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent large cohort study from Brazil similarly found HIV and HCV coinfection to be independent predictors of mortality in PLHTLV (HR 15.1, 95% CI 5.5–41.3) ( Marcusso et al, 2019 ). This has been hypothesized to be due to the impaired cellular immune responses in HTLV-1-infected T-cells mediated by HTLV-1 bZIP factor (HBZ) induced expression of co-inhibitory molecules (such as PD-1, CTLA-4, and TIGIT) and production of inhibitory cytokines like interleukin-10 (IL-10), leading to ineffective resolutions of infections ( Kozako et al, 2009 ; Sawada et al, 2017 ; Higuchi et al, 2020 ; Tan et al, 2022 ). Interestingly, the immunomodulating effects of HTLV-2 infection are less well understood, with recent studies of HIV/HTLV-2 co-infection suggesting that HTLV-2 may exert a protective effect on survival and slowing rate of disease progression to AIDS, although these results are mixed ( Giacomo et al, 1995 ; Hershow et al, 1996 ; Castro-Sansores et al, 2006 ; Bassani et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retrovirus Human T-cell Leukemia Virus type 1 (HTLV-1) primarily infects T lymphocytes, leading to a range of diseases, including adult T-cell leukemia/lymphoma (ATLL) and various inflammatory diseases ( 1 ). HTLV-1 replication initially involves cell-to-cell transmission followed by clonal expansion of infected cells which is responsible for the persistence of the virus and associated diseases ( 2 ). One of the key viral proteins involved in HTLV-1 infection is the oncoprotein Tax that has been first described as a transcriptional activator interacting with a variety of host cell proteins, including the NF-κB family of transcription factors.…”
Section: Introductionmentioning
confidence: 99%